(NsTANI^ESKAQ PO\MAs (NDLQ FORTEPIANO NOTYs - (Na(B.(NsKRQBINs; (Nk(B.(Ni(B.(NiGUMNOWAs (NREDAKCIQs; (Nq(B.(Ni(B.(NmIL_[TEJNAs (NREDAKCIQs ((NmOSKWAs 1969)
(N|TO KNIGA DLQ FORTEPIANO(B.s
Keywords: (NFORTEPIANOs